Recent advances in 'Trapped Rainbow' techniques for stopping light - K. L. Tsakmakidis; Hess, O. (Optics InfoBase Conference Papers, 2009)
We provide an overview of 'trapped rainbow' techniques for stopping light. We show that guided modes with real propagation consrtant and complex frequency can be 'trapped rainbow'-stopped even in the presence of waveguide losses. © 2009 Optical Society of America.